Oseltamivir-Induced Neuropsychiatric Symptoms in a Patient with Chronic Kidney Disease - Kader, Mohammad Irfan Abdul; K, Faris Hussain; R, Namitha; K S, Alida (Indian Journal of Pharmacy Practice)
Oseltamivir, a Neuraminidase Inhibitor (NAI) frequently prescribed for influenza treatment and prevention, has been linked to several neuropsychiatric side effects, such as delirium, delusions and aberrant behavior. The neuropsychiatric side effects due to the administration of oseltamivir are mainly seen in children and adolescent patients. Case reports of neuropsychiatric problems in older individuals related to oseltamivir are sporadic. We report herein a case of an oseltamivir-related neuropsychiatric event in an older female adult in India, which was retrieved after stopping the drug.
Keywords: Oseltamivir; Neuropsychiatric disorder; Antiviral; CKD; COPD